Hubungan Pengetahuan Pasien Gastritis dengan Kekambuhan Gastritis di Rumah Sakit Medika Lestari - Upi Parida; Adin Syaefudin; Wasiran Wasiran; Indriani Febrishaummy Gunawan (Jurnal Siti Rufaidah, 2024)
Gastritis is a digestive disorder with a high prevalence in Indonesia, primarily influenced by dietary patterns and lifestyle factors. This study aims to analyze the relationship between the level of knowledge of gastritis patients and the recurrence of the disease at Medika Lestari Hospital. The research utilized a descriptive correlation design with a cross-sectional approach, involving 28 gastritis patients as samples, selected through a total sampling technique. Data were collected using questionnaires covering knowledge levels and gastritis recurrence status and analyzed using the Chi-Square test. The results showed that the majority of respondents had a good level of knowledge (60.7%) and did not experience recurrence (60.7%). Bivariate analysis indicated a significant relationship between patients’ knowledge levels and gastritis recurrence (p-value = 0.034). Patients with low knowledge were more likely to experience recurrence (25%) compared to those with good knowledge (14.3%). These findings suggest that higher knowledge levels contribute to reducing the risk of gastritis recurrence. This study highlights the importance of health education as part of gastritis management strategies. Hospitals are encouraged to enhance patient education programs to lower recurrence rates and improve patients' quality of life.